Angiotensin and Neurovascular Coupling: Beyond Hypertension. (April 2015) - Bloch, Sherri; Obari, Dima; Girouard, Hélène
Abstract Brain homeostasis is dependent upon the constant perfusion of oxygen and nutrients through CBF. The mechanism responsible to couple CBF to neuronal activity is termed NVC. Ang II, a key player in hypertension, impairs NVC and has been found to be of significant importance in neurodegenerative diseases, such as AD. The presence of Ang II and its metabolites, as well as their receptors have been detected in many areas of the brain. Findings indicate that disruption of NVC by Ang II is mediated by its AT1R and NADPH oxidase (NOX)‐dependent ROS production independently of its effect on blood pressure. Although the process causing ROS to interfere with NVC has yet to be elucidated, data label peroxynitrite as the leading ROS to do so. The same common pathway is involved in NVC impairment in AD experimental models. This review investigates recent data concerning the effects of Ang II on NVC with the intent of exploring new treatment perspectives for neurodegenerative diseases such as AD.